The long haul: Lived experiences of survivors following different treatments for advanced colorectal cancer: A qualitative study. (June 2022) - Lim, Chloe Yi Shing; Laidsaar-Powell, Rebekah C.; Young, Jane M.; Solomon, Michael; Steffens, Daniel; Yeo, David; Blinman, Prunella; Koczwara, Bogda; Joshy, Grace; Butow, Phyllis
Abstract: Purpose: Modern treatments, including surgery and palliative chemotherapy without surgery, enable longer survival for people with advanced/recurrent colorectal cancer (CRC). Qualitative research comparing the physical and psychosocial outcomes of these different treatments is lacking. This study therefore aimed to explore and compare the physical and psychosocial challenges and survivorship experiences of people who receive different treatments for advanced CRC, through a qualitative study. Method: Adults with CRC who have undergone treatment for advanced/recurrent CRC were recruited 0.5–2 years post-surgery or, for palliative chemotherapy participants, 0.5–2 years post-diagnosis of advanced CRC. Qualitative semi-structured telephone interviews, analysed via framework analysis, explored quality of life (QoL) experiences. Demographic, clinical, and QoL data (Functional Assessment of Cancer Therapy – Colorectal (FACT-C), Distress Thermometer) were collected to characterise the sample and inform the framework analysis. Results: A diverse sample of 38 participants (22 female) participated, with ages ranging 27–84 (Median = 59), FACT-C 56–132 (Median = 102), and distress 0–10 (median = 3). Analysis of interviews revealed three overarching themes: 1) the overwhelming impact of protracted, complex illness ; 2) compounding and interacting effects of multiple treatments, impacts, and multimorbidity ; and 3) the long haul is unpredictable, bumpy, and wearing. These themes reveal that people with advanced CRC experience many challenges due to the complex nature of the illness, its treatment, and side effects. Conclusions: Survivors require continued multi-disciplinary supportive care throughout follow-up to manage survivorship challenges. Guideline-led survivorship care and routine monitoring of physical and psychosocial wellbeing throughout follow up is imperative to manage patient expectations and support advanced CRC survivors. Highlights: Survivors of advanced colorectal cancer experience many challenges in survivorship. Pelvic exenteration survivors may require tailored care for their unique challenges. Treatment complexity makes survival an unpredictable, bumpy, and wearing long haul. We need tailored services to meet the needs of advanced colorectal cancer survivors.